IMPACT OF INVESTMENT, LABOR, AND INFRASTRUCTURE ON JAVA ISLAND ECONOMIC GROWTH 2011-2017 - Sari, Maya Aprilia (Universitas Negeri Semarang, 2018)
The study aims to determine and analyze the effect of investment, labor, and infrastructure on economic growth in Java in 2011-2017. This research is a quantitative study using secondary data from six provinces in Java (DKI Jakarta, West Java, Central Java, Special Region of Yogyakarta, East Java and Banten) obtained from the Central Statistics Agency. Analysis of the data used in this study is panel regression of fixed effect model data using the General Least Square (GLS) method. The results showed that individually the domestic investment variable, labor, clean water infrastructure had a significant influence on economic growth while foreign investment had no significant effect on economic growth. Suggestions: 1) local governments are expected to increase the potential of each region to attract investors; 2) local governments are expected to create a conducive investment climate and facilitate investment licensing; 3) local governments are expected to increase the allocation of education funds and provide training in foreign languages ??and skills to the workforce; 4) local governments should make better plans for the distribution of clean water and improve the efficiency of the use of clean water.© 2019, Universitas Negeri Semarang Penelitian bertujuan untuk mengetahui dan menganalisis pengaruh investasi,tenaga kerja, dan infrastruktur terhadap pertumbuhan ekonomi di Pulau Jawa tahun 2011-2017. Penelitian ini merupakan penelitian kuantitatif menggunakan data sekunder enam provinsi di Pulau Jawa (DKI Jakarta, Jawa Barat, Jawa Tengah, Daerah Istimewa Yogyakarta, Jawa Timur, dan Banten) yang diperoleh dari Badan Pusat Statistik.Analisis data yang digunakan pada penelitian ini adalah regresi data panel model fixed effect menggunakan metode General Least Square (GLS). Hasil penelitian menunjukkan bahwa secara individu variabel penanaman modal dalam negeri, tenaga kerja, infrastruktur air bersih memiliki pengaruh signifikanterhadap pertumbuhan ekonomi sedangkanpenanaman modal luar negeri tidak berpengaruh signifikan terhadap pertumbuhan ekonomi. Saran: 1) pemerintah daerah diharapkan meningkatkan potensi setiap daerah agar menarik para investor; 2) pemerintah daerah diharapkan menciptakan iklim investasi yang kondusif dan mempermudah perizinan investasi; 3) pemerintah daerah diharapkan meningkatkan alokasi dana pendidikan dan memberikan pelatihan bahasa asing dan ketrampilan kepada tenaga kerja; 4) pemerintah daerah hendaknya membuat perencanaan distribusi air bersih yang lebih baik lagi dan meningkatkan efisiensi penggunaan air bersih.